2010
DOI: 10.17533/udea.acbi.4727
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad de lepidópteros diurnos en un área de bosque seco tropical del occidente antioqueño

Abstract: Los paisajes rurales albergan muchas especies silvestres y complementan la estrategia de conservación en las áreas naturales protegidas. Esta investigación se planteó dos preguntas: a) ¿Cual es la diversidad de mariposas diurnas de la granja del Politécnico JIC?, b) ¿De las especies encontradas qué proporción han sido referenciadas como indicadoras de bosques? Se dividió la granja en cinco zonas, en las cuales se realizaron once muestreos durante doce meses. Se determinó la diversidad esperada a través de esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Nymphalidae was the most representative family regarding the number of individuals and species recorded in most studies in Colombia. At the Patía River Basin, Millan, et al [67], Gaviria-Ortiz and Henao-Bañol [68], and Henao-Bañol and Andrade-C [69] registered 60 and 90 species, respectively, while Orozco, et al [70] identified 78. In the Magdalena River Valley, Peña and Reinoso [71] found 64 species, and Prince-Chacon, et al [72] reported 38 in the Caribbean plains.…”
Section: Taxonomic Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nymphalidae was the most representative family regarding the number of individuals and species recorded in most studies in Colombia. At the Patía River Basin, Millan, et al [67], Gaviria-Ortiz and Henao-Bañol [68], and Henao-Bañol and Andrade-C [69] registered 60 and 90 species, respectively, while Orozco, et al [70] identified 78. In the Magdalena River Valley, Peña and Reinoso [71] found 64 species, and Prince-Chacon, et al [72] reported 38 in the Caribbean plains.…”
Section: Taxonomic Compositionmentioning
confidence: 99%
“…Lamas (2004) pointed out that Riodinidae have the highest richness after Nymphalidae. However, besides Riodinidae, species from the Lycaenidae family have also been reported with the lowest richness in other studies of butterflies in the tropical dry forest [70,73], mainly due to their small size and dark colors [74]. In addition, most of the species of these families tend to fly in higher strata and rest in the upper part of the trees, making their capture in forest areas difficult [75].…”
Section: Taxonomic Compositionmentioning
confidence: 99%
See 1 more Smart Citation